Dynamic changes of aroma substances during fruit development of six sweet cherry varieties in Qinghai - HAO Shuaiqi; GUO Qingyun; LI Linhao; YUAN Huaning (Guoshu xuebao)
[Objective] Sweet cherry is a large-fruited, colorful, delicious, nutritious and popular among consumers, and the cultivation of sweet cherry in Qinghai province started in 1994, and began to plant on a large scale after 2000, with a cultivated area of about 2173.3 hm2, which has been becoming a characteristic fruit industry in Qinghai province in recent years. And sweet cherry flavor plays a very important role in the consumer's preference, with the maturity of the fruit, the fruit will undergo extremely complex physiological and biochemical metabolic processes, and the volatile aroma compounds also change in the fruit. Therefore, the developmental period is a key factor affecting the production and accumulation of fruit aroma. To identify the aroma compounds in different varieties of sweet cherry fruits from the Qinghai province and to investigate the changes of these compounds at different fruit developmental stages. [Methods] Fruits from six sweet cherry varieties, including Moreau, Qingying No. 1, Celeste, 2018-20, Sweetheart and Rainier, were used as experimental materials. Aroma compounds were analyzed with headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS) at four developmental stages, shell-hardening stage (HS), veraison stage (VE), commercial maturity stage (CMP) and full ripening stage (RP, respectively). The variations in aroma compounds among these six varieties were compared using Venn diagrams, heatmap clustering analysis and principal component analysis (PCA). Partial least squares discriminant analysis (PLS-DA) was applied to screen out differential aroma compounds and to analyze changes in their concentrations at different developmental stages. [Results] A total of 108 aroma compounds were identified across the four developmental stages in the six sweet cherry varieties, with 14 common aroma compounds. Specifically, 69, 46, 45 and 32 aroma compounds were detected at HS, VE, CMP and RP stages, respectively. During cherry fruit development, Moreau showed a trend where aroma compound concentrations first increased and then decreased. Qingying No. 1 and Sweetheart displayed an increase, followed by a decrease and then another increase. The 2018-20 variety exhibited a gradual decrease, reaching the lowest concentration at RP stage. In contrast, the Celeste and Rainier showed fluctuations, peaking at RP stage. PLS-DA identified differential compounds with (Variable Importance in Projection) (VIP) values greater than 1, including 2-Hexenal (E), 2-Hexenal, Hexanal and 2-Hexen-1-ol (E). Across different developmental stages of six cherry varieties, 2-Hexenal showed a trend of increasing concentrations from low to high, while 2-Hexenal (E) and 2-Hexen-1-ol (E) displayed a "W-shaped" trend. The concentration of Hexanal generally increased, then decreased, and increased again. The results showed that the six sweet cherry varieties were dominated by aldehydes from HS stage to PR stage; the contents of Moreau aroma substances showed a general tendency of increasing and then decreasing with the development of sweet cherries, among which aldehydes and olefins were the highest at HS stage, which was obviously higher than that of other varieties, and then showed a decreasing tendency, and the lowest contents were found at RP stage. The content of alcohols showed a trend of increasing and then decreasing. Alkane content was the highest at HS stage, slightly decreased at VE stage, increased at CMP stage, and decreased to the lowest at RP stage; 2018-13 varieties roughly showed a trend of first increasing and then decreasing.2018-20 variety of RP content showed a gradual decline to the lowest trend, in which aldehydes showed a first increase and then a decline to the lowest RP content, alkanes showed a first increase and then a decline to the lowest RP content, alkanes showed a first increase and then a decline to the lowest RP content, and enols showed a first increase and then a decline to the lowest RP content. The RP content of Sweetheart variety showed a general trend of increasing and then decreasing to the lowest, with aldehydes and alcohols showing the highest content at VE stage, then decreasing and increasing at RP stage; olefins showed the highest content at HS stage, and then decreased; and the alkanes exhibited an initial increase in RP content, followed by a subsequent decrease, and ultimately showed a renewed increase. Aldehydes content was the highest at HS stage and then decreased slightly; alcohols content decreased and then increased to the peak at RP stage; olefins content was highest at HS stage; alkanes content increased and then decreased and then increased to the peak at RP stage. By partial least squares discriminant analysis, the substances with VIP values greater than 1 were screened out, and 2-hexenal (E)-(trans-2-hexenal), 2-hexenal (2-hexenal), hexanal (hexanal) and 2-hexen-1-ol (E)-(trans-2-hexen-1-ol) were identified as the main differential aroma substances, with 2-hexenal (E) -content being higher, accounting for 63.32% of the total aroma content. The contents of the aroma substances varied at different developmental stages of the six varieties. [Conclusion] The six sweet cherry varieties exhibited distinct patterns in aroma compound changes during fruit development. The most important key aroma compounds identified were 2-Hexenal (E), 2-Hexenal, Hexanal and 2-Hexen-1-ol (E). These findings provide a theoretical foundation for the genetics and breeding of aroma in sweet cherry, as well as for research on aroma synthesis metabolism and molecular biology.